Шляхи впровадження елементів дистанційного навчання - Логінова, Наталія Іванівна; Логинова, Наталья Ивановна; Loginova, Natal'ja (My University, 2005)
The article analyzes distance learning, which is a form of education through information and communication technologies. Were reviewed the elements of distance learning used in traditional educational process in the Odessa National Academy of Law.
Логінова Н. І. Шляхи впровадження елементів дистанційного навчання / Н. І. Логінова // Актуальні проблеми держави і права : зб. наук. пр. /редкол.: С. В. Ківалов (голов. ред.), Ю. М. Оборотов (заст. голов. ред.), Л. Р. Біла (відп. секр.) [та ін.] ; МОН України, ОНЮА. – Одеса : Юрид. л-ра, 2005. – Вип. 25. – С. 639-643.
Keywords: дистанційне навчання; елементи дистанційного навчання; електронні версії дисциплін; навчальний контент; дистанционное обучение; элементы дистанционного обучения; электронные версии дисциплин; учебный контент; distant learning; elements distant learning; electronic versions of the disciplines; educational content